Analysis of the correlation between core competencies of pediatric nurses and occupational benefit perception and its influencing factors - Zhang, Huihui; Wang, Jianxin; Li, Chunhui; Liu, Xinyu; Xiang, Qianmei (Frontiers in Pediatrics, 2025)
PurposeAnalyzed the correlation between core competencies and career benefits in pediatric nurse specialists, and examined the factors influencing core competencies in pediatric nurse specialists. Provided references for pediatric nursing managers to improve nurses’ core competencies and stabilize the standardized training of pediatric nurse specialists.MethodUsing a convenience sampling method, pediatric nurse specialists from Hebei Children's Hospital, Qinhuangdao Maternal and Child Health Hospital, and Baoding Children's Hospital were selected as study subjects between August and September 2023. A questionnaire survey was conducted using a general information questionnaire, a career benefit scale, and a specialist pediatric nurse core competency scale. Pearson correlation and multiple linear regression analyses were employed to examine relationships and influencing factors.ResultsThe total score of career benefits perception for the 128 pediatric nurse specialists was 117.72 ± 12.34, and the total score of core competencies was 132.23 ± 18.96, both of which were above-average. There were significant differences in the total core competency scores among pediatric nurse specialists of different ages, years of work experience, technical titles, and employment forms. There was a significant positive correlation between the core competencies of pediatric nurse specialists and each dimension of career benefits perception (p < 0.01). Multiple linear regression analysis showed that employment form, years of work experience, and total score of career benefits perception were independent influencing factors of the core competencies of pediatric nurse specialists.ConclusionThe career benefits perception and core competencies of pediatric nurse specialists are both at an above-average level, with a close and mutually influential relationship. The form of employment, years of experience, and total score of career benefits influence the core competencies of pediatric nurse specialists. Nursing managers should take targeted intervention measures based on these influencing factors to improve the core competencies of pediatric nurse specialists.